Migration of adult male children and associated depression among community‐dwelling older parents: A cross‐sectional gender analysis from Longitudinal Ageing Study in India, 2017–2018. (11th January 2022) - Muhammad, Thalil; Sulaiman, Madathil K.; Srivastava, Shobhit
Abstract: Objectives: This study empirically examines the association of migration of an adult male child (ren) on the mental health of the older parents left behind. It also examines the interaction effects of sex of older parents and male child migration on major depression to explore whether there is a gender differential in the possible association. Methods: The data for this study were obtained from the first wave of the Longitudinal Ageing Study in India (LASI, 2017–2018). The total sample size for the present study was 27, 248 older adults aged 60 years and above (male‐12, 624; female‐14, 624). Descriptive statistics along with cross‐tabulation were presented. Proportion test was used to evaluate the significance level of differences in depression by sex. Additionally, binary logistic regression analysis was used to find out the associations. Major depression with symptoms of dysphoria, was calculated using the Short‐Form Composite International Diagnostic Interview (CIDI‐SF). Results: About 10.5% and 9.0% of older males and females had migrant sons. It was found that there was significant gender differential in depression in older age (male: 7.5% and female: 9.7%; p < 0.001). It was further found that the prevalence of depression was found among older men (9.3% vs. 7.3%) and women (12.5% vs. 9.4%) with migrant son. Older adults with migrant son had 26% significantly higher likelihood to be depressed in reference to older adults with non‐migrant son (AOR: 1.26; CI: 1.02–1.56). Further, older women with a migrant son had 76% significantly higher likelihood to be depressed in reference to older men with migrant son (AOR: 1.76; CI: 1.32–2.39). Conclusions: This study invites policymakers' attention towards migration of adult children and its potential effects on mental health of left‐behind older parents in community‐settings and in women in particular. Policies should focus on spreading awareness to migrant children of older adults on maintaining frequent contacts and visits to their ageing parents. Key points: This cross‐sectional study of a nationally representative survey data found a proportion of 10.5% and 9.0% of older men and older women having migrant sons in India There was a significant gender difference in the prevalence of depression in older individuals with 7.5% of men and 9.7% of women being depressed Older adults with migrant sons had a higher likelihood to be depressed than older adults with non‐migrant sons The study invites policymakers' attention towards migration of adult children and its potential effects on mental health of left‐behind older parents and women in particular